Effect of Mixing Time Variation and Framing Time on the Quality of Coffee Grounds-based Solid Soap - Neisya, Insa Dorra; Suratno, Suratno; Fikri, Kamalia (Biology, Medicine, & Natural Product Chemistry, 2024)
The increase in public consumption of coffee has resulted in an increase in wasted coffee grounds. Coffee grounds have good content for the skin, so they can be reused as a basic ingredient in soap-making. In the soap making process, the mixing and framing stages can affect the quality of the soap. This study aims to determine the effect of mixing time of 24.5 minutes, 25 minutes, and 25.5 minutes as well as framing time of 3 days, 5 days, and 7 days on the physical and chemical quality of solid soap made from coffee grounds. The physical quality parameters observed are colour, texture, cracking, and foam power. The chemical quality parameters are foam stability, pH, moisture content, and free alkali. The method used was the questionnaire method followed by statistical analysis using the Kruskal Wallis test for physical quality tests and the experimental method followed by statistical analysis using the Two-Way ANOVA test for chemical quality tests. The results showed that all variations in mixing time and framing time had an effect on the physical and chemical quality of solid soap and there were significant differences. The panellists assessed the physical quality of the soap to be attractive, hard, with no cracks, and foamy, while the results of the chemical quality test, the soap produced is safe to use by the quality standards of solid soap with a foam stability range of 82%-97%, pH 10.3-11.8, moisture content 6%-14%, and alkali free 0.03%-0.09%.